Semi-aromatic biobased polyesters derived from lignin and cyclic carbonates. Issue 23 (12th November 2021) - Winfield, DeMichael; Ring, John; Horn, Jessica; White, Evan M.; Locklin, Jason
Abstract : Synthesis, characterization, and compostability of several biobased polyesters with a wide array of thermoplastic and elastic properties are described. Abstract : The synthesis of biobased aromatic polyesters from lignin-derived monomers has become well described in the literature, but robust extrusion, thermomechanical, tensile and degradation studies of these materials is lacking. In this work, we have systematically investigated the mechanical and biodegradation properties of semi-aromatic polyesters that can potentially be derived from lignin. AB monomers were synthesized from reduced analogues of coumaric, ferulic, and sinapic acids along with cyclic carbonates, where the synthetic methodology was assessed using E-Factor and EcoScale. Polymerization yielded both semi-crystalline and amorphous polyesters with mechanical properties varying over three orders of magnitude. Detailed characterization revealed a wide array of properties including a highly ductile thermoplastic, a strong and rigid thermoplastic, and an elastomer. Composting biodegradation tests showed both degradable and nondegradable polymers can be achieved in this class. This work demonstrates the versatility of this class of polymers and illustrates their potential to replace non-sustainably derived plastics.